Prácticas seguras en estudiantes de externado de la carrera de enfermería de Uniandes-Tulcán - Mena Ger, Marcelo Alexander (2025)
Safe practices are essential for protecting patients and health personnel, for improving the quality service, reducing medical errors and guaranteeing the accomplishments of regulated and normed practices, this is the reason that this research involves the intervention of externship students from the University Uniandes campus Tulcán, whose main objective was to develop educational strategies for the adequate management of safety practices. The research was developed under a quantitative approach, theoretical methods of study such as analytic - synthetic with a systemic approach, similarly, empiric methods of knowledge such as the documentary analysis were used, thus resulting in setting the problem in context, regarding the population studied it was comprised of 130 students of the externship program and the survey was the technique carried out to collect the data. The most relevant results showed that 68% of the population do not know about administrative safety practices, in addition 60% is unaware of the safe care practices, and 45% do not remember about safe administrative or care practices; these previous data allowed to support the creation of a proposal by using educational strategies called “Take care safely, protect with quality” feasible for the students of external nursing practices, alongside that it will contribute to their pre professional practices in response to the problem identified where real information was established towards the need to straighten and consolidate knowledge regarding safe practices.